Identification of Potential Inhibitors of PDE5 based on Structure-based Virtual Screening Approaches - Xu, Lei; Sun, Lilei; Su, Peng; Ma, Teng; Yu, Yingcong; Liu, Haibin; Huang, Xianfeng (Current Computer - Aided Drug Design, 2023)
Background: Phosphodiesterase type 5 (PDE5), exclusively specific for cyclic guanidine monophosphate (cGMP), a potential target for the therapy of various diseases, and PDE5 inhibitors could be used as a treatment for erectile dysfunction (ED) or chronic pulmonary hypertension. Objective: In the present study, we carried out an integrated computer-aided virtual screening technique against the natural products in the ZINC database to discover potential inhibitors of PDE5. Methods: Pharmacophore, molecular docking and ADMET (Absorption, distribution, metabolism, excretion and toxicity) properties filtration were used to select the PDE5 inhibitors with the best binding affinities and drug-like properties. The binding modes of PDE5 inhibitors were investigated, and these complexes' stabilities were explored by molecular dynamic simulations and MM/GBSA free energy calculations. Results: Two natural compounds (Z171 and Z283) were identified and may be used as a critical starting point for the development of novel PDE5 inhibitors. The MM/GBSA free energy decomposition analysis quantitatively analyzed the importance of hydrophobic interaction in PDE5- ligands binding. Conclusion: In this study, we identified two novel natural compounds from the ZINC database to effectively inhibit PDE5 through virtual screening. The novel scaffolds of these compounds can be used as the starting templates in the drug design of PDE5 inhibitors with good pharmacokinetic profiles. These results may promote the de novo design of new compounds against PDE5.
Keywords: molecular docking